Takotsubo syndrome: a way to reach a straightforward diagnosis. (14th October 2021) - Bonanni, A; Pedicino, D; Vinci, R; D'Aiello, A; Ponzo, M; Ciampi, P; Pisano, E; Canonico, F; Di Sario, M; Conte, C; Cribari, F; Grimaldi, M C; et al.
Abstract: Background/Introduction: Acute stress-induced cardiomyopathy, also known as Takotsubo Syndrome (TTS), was originally classified as a benign disease. Nowadays, this assumption has changed, especially in its long-term outcome, due to TTS clinical presentation, that often mirrors the acute myocardial infarction (MI) phenotype. Current knowledge already delineate clinical features distinctive of TTS and MI patients, however, diagnosis requires multiple, expansive, and invasive medical examinations. Moreover, concerning the biological panorama, very slight is known and the lack of a tailored therapy is resented. Therefore, a biological profile for this clinical category could provide easier and less invasive diagnostic tools, leading edge towards novel therapeutic pathways. Purpose: The aim of the study is to perform a biological profile of the TTS group compared to the ST Segment Elevation Myocardial Infarction (STEMI) in order to explore the molecular peculiarities attendant the pathophysiologic mechanisms. Methods: We performed a gene expression array on two groups of pooled cDNA from peripheral blood mononuclear cells, from TTS (n=11) and STEMI (n=19) patients. We conducted gene expression validations for each enrolled patient through qPCR. Results: Our preliminary data displayed several differences in gene expression levels of a grand number of cell adhesion signaling molecule between the two groups. As shown in figure 1, three gene were more expressed in TTS group: Nitric Oxide Synthase 3, also known as endothelial NOS (NOS3; p=0.002), Superoxide dismutase 1 (SOD1; p=0.03) and transferrin receptor (TFRC; p=0.005). Meanwhile, five gene displayed a higher expression in STEMI patients compared to TTS: phospholipase A2 Group 7 (PLA2G7; p=0.04), Galectin 8 (LGALS8; p=0.02), Intercellular Adhesion Molecule 1 (ICAM1; p=0.002), Hyaluronidase 2 (HYAL2; p=0.01) and Hyaluronan Receptor (CD44; p=0.0002). Conclusions: The earliest results of this study led us to focus on fewer genes related to endothelial and oxidative stress pathways. TTS is habitually triggered by intense emotional or physical stress. Indeed, our results showed how TTS patients present higher expression of NOS3, SOD1 and TFRC, all components involved in the oxidative stress pathways. In STEMI patients, top expressed genes, such as HYAL2, CD44 and ICAM1, are all associated with extracellular matrix turnover, likely due to the presence of a stenotic plaque and the consequent endothelial derangement. The uncovering of diagnostic biomarkers in TTS might improve the early, non-invasive, stratification of this group of patients, thus facilitating novel and personalized therapeutics design. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The present study was supported by the Italian National Project Grant PRIN 2017.